Phenylpropanoids from Brachybotrys paridiformis Maxim. ex Oliv. and their anti-HBV activities. (May 2022) - Wu, Si-Tong; Wang, Yi-Xiao; Yu, Bai-Hong; Ma, Chun-Liu; Qiu, He-Qin; Wang, Guang-Shu
Abstract: Using chemical and spectroscopic data, this study on Brachybotrys paridiformis Maxim. ex Oliv. identified four undescribed phenylpropanoids, brachin A–C and brachoside A, together with nine other known compounds. The isolated compounds were tested for anti-hepatitis B virus activities in the HepG2.2.15 cell line. Among them, caffeic anhydride showed the most potent activity. Graphical abstract: Four undescribed phenylpropanoids and nine known compounds were isolated from Brachybotrys paridiformis Maxim. ex Oliv. Their anti HBV activities were studied. The picture of B. Paridiformis was obtained from the Plant Photo Bank of China. Image 1 Highlights: Four undescribed compounds were obtained from Brachybotrys paridiformis Maxim. ex Oliv. Main components isolated from this plant were phenylpropanoids and its derivatives. The anti-HBV activities of the isolated compounds are reported.